Role of pH and Nitrogen Limitation in the Elaboration of the Extracellular Polysaccharide Pullulan by Pullularia pullulans - Catley, B. J. (1971)
During the growth of the yeastlike fungus Pullularia pullulans on glucose as sole carbon source, the cell-mass does not increase concomitantly with the elaboration of the extracellular polysaccharide pullulan, but precedes it. The conditions generated in the culture medium which activate the secretion of polysaccharide have been sought for, and, in particular, the roles of extracellular pH and nitrogen limitatation are examined.